Electric control of magnetism in a multiferroic metal–organic framework. Issue 1 (7th November 2013) - Tian, Ying; Cong, Junzhuang; Shen, Shipeng; Chai, Yisheng; Yan, Liqin; Wang, Shouguo; Sun, Young
Abstract Electric control of magnetism is demonstrated in a multiferroic metal–organic framework with a perovskite structure. A moderate electric field of a few kV/cm applied during the cooling process is able to cause a large (more than 50%) change of the magnetization at low temperature. This significant magnetoelectric effect is ascribed to the electric field manipulation of orientation of hydrogen bonds that modify the superexchange interaction between metal ions. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text> Electric‐field cooling causes a large change in the magnetization of a multiferroic MOF. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)